Nazi Gender Ideology, Memoricide, and the Attack on the Berlin Institute for Sexual Research. (2nd October 2022) - Fuller, Matt; Owen, Leah
Abstract : On 6 May 1933, a group of Nazi students attacked and looted the Institute for Sexual Research (the Institut für Sexualwissenschaft, or "IfS"), a body set up by the Jewish and openly gay sexologist, Magnus Hirschfeld. The IfS' archives were publicly burned four days later (Hill 2013, 13–15), with photos of the event now synonymous with Nazi repression. Was this targeted, categorical, exterminatory violence against LGBTQ people an attempt at "memoricide" – the willful destruction of the memories and cultural treasures of an adversary (Civallero 2007 )? This paper argues that queer people – including trans people – were indeed attacked as part of the Holocaust, facing specific attempts to erase them (whether through invisibilization, memoricide, or direct extermination). Nazi anti-queer ideology, however, was incoherent and erratic. This study contests that they attempted memoricide, social cleansing, and genocide of groups whose parameters and "threat" they had only a hazy notion of. This led to inconsistent treatment for what we might now describe as "transfeminine" and "transmasculine" populations, and produced complex and ad hoc, but still deeply queerphobic, state discourse. Having examined these patterns of prejudice, we proceed to examine attempts to restore this history, and recount the lives of trans people and archives.